(untitled) (Psikologiya Journal, 2025)
The rapid growth of live streaming gaming has transformed how young people experience reality, creating immersive digital environments that increasingly blur the boundary between virtual and real life. This phenomenon generates complex implications for youth mental health, functioning both as a source of emotional support and as a psychosocial risk factor. This study aims to explore young people’s experiences in live streaming gaming, the process of reality blurring, and its implications for mental health and psychosocial functioning. Using a qualitative interpretative phenomenological approach, in-depth interviews were conducted with young adults aged 18–30 actively engaged in live streaming gaming. Data were analyzed through thematic analysis to identify experiential patterns, psychological dynamics, and adaptive mechanisms. The findings indicate that blurred reality emerges through digital immersion, emotional attachment, and parasocial relationships, producing ambivalent mental health outcomes. While live streaming fosters emotional support and a sense of belonging, excessive involvement heightens the risks of anxiety, depression, sleep disturbances, and social dysfunction. The study highlights the urgent need for multidimensional interventions involving individuals, families, educational institutions, digital communities, and public policy to cultivate a healthy digital ecosystem for youth.